Anatomical Variation of the Axillary Artery in Central Punjab Population of Pakistan - Yasmeen Bashir, Saira Munawar, Uzma Waseem, Amina Liaqat, Samia Shahbaz, Aneeqa Chughtai (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Axillary artery continues directly from subclavian artery. It usually provides six branches in three parts. Superior thoracic artery is provided by first part of axillary artery whereas the second part provides thoracoacromial artery (TAC) and lateral thoracic artery (LT) and third part provides posterior circumflex humeral artery (PCH), anterior circumflex humeral artery (ACH) and subscapular artery (SS). This branching pattern of axillary artery usually involves anatomical variation and typically inofvolves posterior circumflex humeral artery, lateral thoracic artery and subscapular artery. The variation in this pattern contains surgical and clinical as well as anatomical relevance given the accessibility towards humerus and shoulder joint. Methodology: This study (bilateral axilla dissection) was performed on 28 preserved axillae (14 dead bodies) to permit axillary artery’s examination and its parts. The study was conducted in anatomy department, Services Institute of Medical Sciences, Lahore, from November 2022 to April 2023. Results: 76% of cases showed the characteristic branching pattern of the LT, which originates from the axillary artery posterior to the pectoralis minor muscle, and the SS, which produces the thoracodorsal (TD) and circumflex scapular (CS) arteries. 8% of the time, it was noticed that the SS originated from the LT. Six percent of the time, the LT was seen to be coming from the SS. In the absence of SS, the LT was seen to produce the TD and circumflex scapular artery 3% of the time. According to 76% of classical descriptions, the PCH developed from four distinct sources, the third portion of the axillary artery. 12% from the SS. from the DB 8% deep brachial artery and the LT 3%. Conclusion: It is rather typical for the axillary artery and its branches to have vascular diversity. As this variation can increase the risk of bleeding during surgery of axilla so it is crucial to consider it seriously. It can also cause difficulty in angiography interpretation after axillary catheterization. Keywords: Anatomy of axilla, axillary artery, variation in axilla and vascular variation, lateral thoracic artery (LT), subscapular artery (SS), posterior circumflex humeral artery (PCH).